Hepatocellular carcinomas with intracellular hyaline bodies have a poor prognosis. (12th January 2017) - Aigelsreiter, Ariane; Neumann, Jens; Pichler, Martin; Halasz, Judith; Zatloukal, Kurt; Berghold, Andrea; Douschan, Philipp; Rainer, Florian; Stauber, Rudolf; Haybaeck, Johannes; Denk, Helmut; Lackner, Carolin
Abstract: Background & Aims: Mallory‐Denk bodies (MDBs) and intracellular hyaline bodies (IHBs) are cytoplasmic inclusions found in a subset of hepatocellular carcinoma (HCC). MDBs are mainly composed of the intermediate filament proteins keratin (K) 8 and K18, the cellular stress‐ and adapter‐protein sequestosome 1/p62 (p62) and ubiquitin, whereas IHBs consist of p62 and/or ubiquitin. Of note, cytoplasmic inclusions containing p62 can serve as markers of suppressed autophagy, which in turn has been associated with poor prognosis. The aim of this study was to evaluate the prognostic significance of p62‐containing MDB and IHB in patients with HCC. Methods: Ninety resected HCCs were assessed by H&E histology for MDB or IHB, and their presence was confirmed by immunohistochemistry using K8/18, p62 and ubiquitin antibodies. The prognostic impact of inclusions was assessed using Kaplan‐Meier and multivariate Cox proportional model. Results: Mallory‐Denk bodies and/or IHB were found in about 50% of HCC. Both types of inclusions were seen in 21%, MDB only in 19% and IHB only in 10% of cases. The presence of MDB in tumours was associated with the steatohepatitic variant of HCC, which also showed fatty change, ballooning of tumour cells, MDBs, inflammation and pericellular fibrosis ( P <.001). In contrast, IHBs were not associated with steatohepatitic morphology but were associated with significantly shorter overall survival ( P =.006). Multivariate analysis revealed macroscopic vascular invasion ( P =.045) and presence of IHB in HCC cells ( P =.005) as independently associated with overall survival. Conclusions: Intracellular hyaline bodies and macroscopic vascular invasion identify a subset of HCC patients with poor prognosis.